Let "y=\\sum\\limits_{n=0}^{\\infty}a_nx^n"
Then
"y'=\\sum\\limits_{n=1}^{\\infty}na_{n}x^{n-1}"
"y''=\\sum\\limits_{n=2}^{\\infty}n(n-1)a_{n}x^{n-2}"
After reidexing the series, we will have
"y'=\\sum\\limits_{n=0}^{\\infty}(n+1)a_{n+1}x^{n}"
"y''=\\sum\\limits_{n=0}^{\\infty}(n+2)(n+1)a_{n+2}x^{n}"
Plugging "y'" and "y''" into the equation will lead us to
"(x^2-1)\\sum\\limits_{n=0}^{\\infty}(n+2)(n+1)a_{n+2}x^{n}+3x\\sum\\limits_{n=0}^{\\infty}(n+1)a_{n+1}x^{n}+x\\sum\\limits_{n=0}^{\\infty}a_nx^n=0"
"\\sum\\limits_{n=0}^{\\infty}(n+2)(n+1)a_{n+2}x^{n+2}-\\sum\\limits_{n=0}^{\\infty}(n+2)(n+1)a_{n+2}x^{n}+\\sum\\limits_{n=0}^{\\infty}3(n+1)a_{n+1}x^{n+1}+\\sum\\limits_{n=0}^{\\infty}a_nx^{n+1}=0"
Let's transform the series in the right hand side
"2a_2+(6a_3+3a_1+a_0)x+\\sum\\limits_{n=2}^{\\infty}n(n-1)a_{n}x^{n}-\\sum\\limits_{n=2}^{\\infty}(n+2)(n+1)a_{n+2}x^{n}+"
"+\\sum\\limits_{n=2}^{\\infty}\\left(3na_{n}+a_{n-1}\\right)x^{n}=2a_2+(6a_3+3a_1+a_0)x+\\sum\\limits_{n=2}^{\\infty}\\left(n(n-1)a_{n}+(n+2)(n+1)a_{n+2}+\\right."
"\\left.+3na_{n}+a_{n-1}\\right)x^n"
As this series is supposed to be equal to 0, we know that the coefficients of the resulting series must be equal to 0. Therefore,
"2a_2=0"
"6a_3+3a_1+a_0=0"
"n(n-1)a_{n}+(n+2)(n+1)a_{n+2}+3na_{n}+a_{n-1}=0.\\quad n\\ge2"
"(n^2+2n)a_n+(n+2)(n+1)a_{n+2}+a_{n-1}=0"
"a_{n+2}=-\\frac{(n^2+2n)a_n+a_{n-1})}{(n+2)(n+1)}"
Plug in "a_0=0;\\quad a_1=1" we find the first solution
"6a_3+3=0\\quad a_3=-\\frac{1}{2}"
"a_{4}=-\\frac{(2^2+4)a_2+a_{1})}{(2+2)(2+1)}=-\\frac{1}{12}"
"a_5=-\\frac{(9+6)a_3+a_2}{(3+2)(3+1)}=-\\frac{-\\frac{15}{2}}{20}=\\frac{3}{8}"
"a_6=-\\frac{(14+8)a_4+a_3}{(4+2)(4+1)}=-\\frac{-\\frac{22}{12}-\\frac{1}{2}}{30}=\\frac{7}{90}"
Therefore
"y_1=x-\\frac{1}{2}x^3-\\frac{1}{12}x^4+\\frac{3}{8}x^5+\\frac{7}{90}x^6+..."
Plug in "a_0=1,\\quad a_1=0" we find the second solution
"6a_3+1=0\\quad a_3=-\\frac{1}{6}"
"a_{4}=-\\frac{(2^2+4)a_2+a_{1})}{(2+2)(2+1)}=0"
"a_5=-\\frac{(9+6)a_3+a_2}{(3+2)(3+1)}=-\\frac{-\\frac{15}{6}}{20}=\\frac{1}{8}"
"a_6=-\\frac{(14+8)a_4+a_3}{(4+2)(4+1)}=-\\frac{-\\frac{1}{6}}{30}=\\frac{1}{180}"
Therefore
"y_2=1-\\frac{1}{6}x^3+\\frac{1}{8}x^5+\\frac{1}{180}x^6+..."
Comments
Leave a comment